Knowledge and practice on prevention and control of dengue fever among people at Mangalpur VDC, Chitwan district of Nepal - Sah, Naresh Kumar (Journal of Chitwan Medical College, 2021)
Background: In many parts of the tropics and subtropics, dengue is endemic especially during rainfall season which is the breeding season of the Aedes mosquito. The knowledge, attitudes and practices (KAP) of the general population are the most critical factors on preventing the infection of dengue virus. Hence this study was aimed to access the knowledge and practice on prevention and control of Dengue among the people of Mangalpur VDC of Chitwan. Methods: A cross-sectional study was done in Mangalpur VDC, Chitwan district of Nepal from Shrawan 2069 to Bhadra, 2069. The sample size of the study was 345 and respondents were the people of Mangalpur VDC. Data is analyzed by using SPSS program version 16.0 for windows. Results: Majority of the respondents 167(48.4%) were between age group 25-39 and minority 9(2.6%) age group >70 years. The mean age of the respondents is 40 years±11. Out of 345 respondents, 176 (51%) were female and 169 (49%) were male. Majority of respondents 218 (63.2) were literate and 127 (36.8%) were illiterate. The level of knowledge regarding dengue fever was statistically significant with age (p=0.002), marital status (p=0.005), education Status (p=0.010), religion (p=0.003) and with occupation (p=0.000). The level of practice regarding dengue fever was statistically significant with marital status(p=0.003), educational status (p=0.000), occupation(p=0.000) and religion(p=0.258). Conclusions: Lack of knowledge and improper practice towards dengue is explicit in this study. Emphasis should be more on creating awareness among people. Education intervention more effective in controlling dengue fever.